(3HdhZ GdCed aj WQa ef CMeGd GdRLds - (3eMeO Hf eQRhb GdOLhjs
(3ChdgG (B:s
(3hHYO ajbhd (B:(3bO SCdfi HYV ENhGfi GdPjf CeQge YfOi eWdY Cf CLeY cJGHG ai af GdRLd aCLHJg dPdc Ydi YLd hLeYJg hYdi Gddg GYJeGOi hSejJg hQJHJg Ydi ebOeI hNeSI aUhd hNGJeI s
(3BNQgG (B:s
(3eHJhQ ,hBNQ eGajg (B: (3hGf cfJ fTGQ hWHYc bGS Ydjcc eKd GdNTH JeSc HGdhGMO GdCMO hfHjg UahI YOfGf s
(3GdfSNI HgG MhGTs
(3HChdgG agQSJs
(3ceG jhLO HChdg MGTjI Jbhd (B:" (3eShOI hfbdJ HJQJjH HRjGOGJ CNQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B127 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs